CGIAR Research Program on Roots, Tubers and Bananas - Plan of Work and Budget 2020 - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR Research Program on Roots, Tubers and Bananas, 2020)
The impact pathways (see Figure 1) towards the development outcomes remain relevant and, to enhance its effectiveness, the CGIAR Research Program on Roots, Tubers and Bananas (RTB) is pursuing closer coordination and better integration with other CRPs and Platforms and their program participants. Also, following the lead from the System Reference Group and building on the experience gained on both the science and the practice of scaling, RTB is engaging in more systematic use of end-to-end design for innovation management and increased use of stage gating.